Dietas artificiais para a criação de Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae) - Cartaxo , Paulo Henrique de Almeida (2021)
Ceratitis capitata (Wiedemann 1824)(Diptera: Tephritidae) is a polyphagous insect responsible for severe damage to fruit production worldwide. Control strategies require laboratory studies in which large numbers of individuals of this pest are required, thus requiring the implementation of mass creations. The success of these creations depends on the use of artificial diets, which represent one of the main costs of this system. In this sense, this study aimed to evaluate the efficiency of different artificial diets based on regional foods in the development of C. capitata in the laboratory. Eggs of C. capitata were inoculated in artificial diets based on sweet potato, yam, carrot, pumpkin and cassava, all in the raw and cooked version, totaling ten treatments, with raw carrot being the control treatment. Variables related to the biometric and biological characteristics of C. capitata, such as larval and pupal viability, fecundity, fertility and sex ratio, in addition to pre-oviposition, oviposition and adult life times, were evaluated. Promising results were obtained with the use of artificial diets based on regional foods, such as sweet potato and pumpkin, in which higher pupae weight and size, good fecundity and fertility, insects with longer oviposition time and longer longevity were observed, whose results were similar or superior to those obtained with the raw carrot-based diet. In contrast, the raw cassavabased diet did not allow larvae to hatch. Unsatisfactory results were also obtained with diets based on yam, both raw and cooked, which makes its recommendation for use in artificial diets for this insect unfeasible. Artificial diets derived from pumpkin and sweet potato, raw or cooked, are efficient as carrot substitutes in artificial diets of C. capitata.